Aerosol indirect effects on orographic clouds and precipitation - Chavez, Steven P.; Barros, Ana P. (Frontiers in Earth Science, 2023)
The sensitivity of warm orographic cloud development to aerosol indirect effects was investigated through aerosol-aware Weather Research and Forecast model simulations contrasting aerosol-cloud-precipitation interactions using the default (generic) aerosol and regional aerosol measurements from the Integrated Precipitation and Hydrology Experiment in the Southern Appalachian Mountains for three rainfall events: 1) enhanced local convection; 2) a frontal system, and 3) a tropical system. Using the regional aerosol activation spectrum yields higher number of drops than using the default, smaller cloud droplets and delayed rainfall onset under weak synoptic forcing conditions. Evaluation against aircraft measurements in isolated convective clouds reveals that while the model microphysics falls short of reproducing the vertical structure of nonprecipitating clouds, the liquid water content, and the concentration of cloud droplets near cloud base are in keeping with observations. The simulated cloud vertical structure shows the regional signature of orographic enhancement over the mountains vis-a-vis the adjacent plains. In the inner region, valley-ridge circulations organize the spatial patterns of cloudiness under weak synoptic forcing. The formation of early afternoon low-level clouds over the ridges in the summertime reflects the aerosol indirect effect. By contrast, for large-scale systems with strong and sustained moisture convergence at low levels (frontal and tropical systems), mechanically forced rainfall efficiency is enhanced, there is no delay in the onset of precipitation, and the aerosol indirect effect is negligible. This study shows that the impact of aerosol-cloud-precipitation interactions on the spatial variability of orographic rainfall is conditional on weather regime.